Risk Management Maturity A Multidimensional Model - Bąk, Sylwia (Routledge Focus on Business and Management, 2023)
Crises like the COVID-19 pandemic are wake-up calls for enterprises to review their current risk management models. This book suggests a more robust risk management maturity model and illustrates the application in crisis situations. The book surveys existing risk management maturity models and proposes a new model appropriate for assessing the risk management processes in enterprises during times of crisis. Its key advantages include the correlation of its attributes with crisis situations and an innovative methodological approach to model development. The authors use the model to examine 107 enterprises from the financial services, construction and IT sector, showing how it allows the user to identify risk management maturity changes in the aftermath of the COVID-19 pandemic. The book will interest entrepreneurs, managers and risk management professionals, who can use the model in their management processes, as well as enterprise stakeholders and academics.